Re-description of two species of the cardinalfish genus Archamia (Teleostei: Apogonidae) from the Red Sea and Western Indian Ocean - Gon, Ofer; Gouws, Gavin; Mwale, Monica; Mwaluma, James (Zootaxa, 2013)
The cardinalfishes Archamia bilineata and A. pallida were originally described from a small number of specimens collected in the Gulf of Aqaba, Red Sea and Oman, respectively. Both species are re-described using specimens collected recently in Yemen and Kenya, including the first known adult of A. pallida. These new collections increased the geographical range of both species considerably. Differences between the two populations now known for each of the species are discussed.